Molecular dynamics simulation of PNPLA3 I148M polymorphism reveals reduced substrate access to the catalytic cavity1. Issue 3 (5th November 2012) - Xin, Yong‐Ning; Zhao, Yuqi; Lin, Zhong‐Hua; Jiang, Xiangjun; Xuan, Shi‐Ying; Huang, Jingfei
Abstract A missense mutation I148M in PNPLA3 (patatin‐like phospholipase domain‐containing 3 protein) is significantly correlated with nonalcoholic fatty liver disease (NAFLD). To glean insights into mutation's effect on enzymatic activity, we performed molecular dynamics simulation and flexible docking studies. Our data show that the size of the substrate‐access entry site is significantly reduced in mutants, which limits the access of palmitic acid to the catalytic dyad. Besides, the binding free energy calculations suggest low affinity for substrate to mutant enzyme. The substrate‐bound system simulations reveal that the spatial arrangement of palmitic acid is distinct in wild‐type from that in mutant. The substrate recognition specificity is lost due to the loop where the I148M mutation was located. Our results provide strong evidence for the mechanism by which I148M affects the enzyme activity and suggest that mediating the dynamics may offer a potential avenue for NAFLD. Proteins 2013. © 2012 Wiley Periodicals, Inc.